Analisis Collaborative Governance Dalam Penyelenggaraan Pelayanan Publik Pada Samsat Wilayah Kabupaten Natuna - Huda, Nurul; Madya, Faizal; Priyanto, Agus (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Especially in this age of globalization, the government bureaucracy must respond to the community's needs and demands for improved public services. The government agency in charge of vehicle tax services is one of the entities tasked with receiving PAD and sustaining public services. The presence of collaborative governance is a concept utilized by an organization to achieve long-term objectives and effect transformational change. This study's objective was to investigate the application of the concept of collaborative governance in the Regional Samsat of Natuna Regency. This study employs a qualitative methodology for collecting primary data, including interviews and observations. The results showed that the implementation of collaborative governance in the Samsat Office of Natuna Regency was Starting Condition, Collaborative Process, Facilitative Leadership and Institutional Design.